EVALUASI UNJUK KERJA SISTEM PROPULSI MOTOR ROKET RX-150-1200 DENGAN MENGGUNAKAN PIRANTI LUNAK PRODUK LAPAN - Samosir, Ganda (Indonesian Journal of Aerospace, 2007)
The propulsion calculations of the rocket motor RX-150-1200 was done by using the propulsion simulation software developed bya the researchers of the Propulsion Division-LAPAN. The results were compared to that of motor rocket static test to find out the occurary of the motor rocket propulsion system design. Mostly, if there is a difference between those two results are less than 10 percent, we may concluded that the propulsion rocket motor design is correct or pseudo-correct classified, because the deviation obtained in this paper is 1.05 percent only. Keywords: Propulsion, Rocket motor.